Nanofibrous nerve conduit‐enhanced peripheral nerve regeneration. (15th June 2012) - Jiang, Xu; Mi, Ruifa; Hoke, Ahmet; Chew, Sing Yian
Abstract Fibre structures represent a potential class of materials for the formation of synthetic nerve conduits due to their biomimicking architecture. Although the advantages of fibres in enhancing nerve regeneration have been demonstrated, in vivo evaluation of fibre size effect on nerve regeneration remains limited. In this study, we analyzed the effects of fibre diameter of electrospun conduits on peripheral nerve regeneration across a 15‐mm critical defect gap in a rat sciatic nerve injury model. By using an electrospinning technique, fibrous conduits comprised of aligned electrospun poly (ε‐caprolactone) (PCL) microfibers (981 ± 83 nm, Microfiber) or nanofibers (251 ± 32 nm, Nanofiber) were obtained. At three months post implantation, axons regenerated across the defect gap in all animals that received fibrous conduits. In contrast, complete nerve regeneration was not observed in the control group that received empty, non‐porous PCL film conduits (Film). Nanofiber conduits resulted in significantly higher total number of myelinated axons and thicker myelin sheaths compared to Microfiber and Film conduits. Retrograde labeling revealed a significant increase in number of regenerated dorsal root ganglion sensory neurons in the presence of Nanofiber conduits (1.93 ± 0.71 × 103 vs. 0.98 ± 0.30 × 103 in Microfiber, p < 0.01). In addition, the compound muscle action potential (CMAP) amplitudes were higher and distal motor latency values were lower in the Nanofiber conduit group compared to the Microfiber group. This study demonstrated the impact of fibre size on peripheral nerve regeneration. These results could provide useful insights for future nerve guide designs. Copyright © 2012 John Wiley & Sons, Ltd.